2020
DOI: 10.3390/molecules25112682
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape-Dependent Antimicrobial Activities of Silver and Gold Nanoparticles: A Model Study as Potential Fungicides

Abstract: Plant-based pathogenic microbes hinder the yield and quality of food production. Plant diseases have caused an increase in food costs due to crop destruction. There is a need to develop novel methods that can target and mitigate pathogenic microbes. This study focuses on investigating the effects of luteolin tetraphosphate derived silver nanoparticles (LTP-AgNPs) and gold nanoparticles (LTP-AuNPs) as a therapeutic agent on the growth and expression of plant-based bacteria and fungi. In this study, the silver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 51 publications
(54 reference statements)
2
34
0
Order By: Relevance
“…Nanoparticles with size < 10 nm can penetrate to the interior of the bacterial cell and exert their antibacterial effect (Khalandi et al 2017), while that > 10 nm cannot penetrate the interior of the bacterial cell (Butler et al 2015;Wang et al 2011). A recent investigation by Osonga et al (2020) reported that the antimicrobial activities of AgNps and AuNps were dependent on size, with no associated toxicity. Furthermore, the surface charge of nanoparticles is also a crucial factor affecting their antimicrobial activity (Abbaszadegan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles with size < 10 nm can penetrate to the interior of the bacterial cell and exert their antibacterial effect (Khalandi et al 2017), while that > 10 nm cannot penetrate the interior of the bacterial cell (Butler et al 2015;Wang et al 2011). A recent investigation by Osonga et al (2020) reported that the antimicrobial activities of AgNps and AuNps were dependent on size, with no associated toxicity. Furthermore, the surface charge of nanoparticles is also a crucial factor affecting their antimicrobial activity (Abbaszadegan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles (Ag NPs) are considered to be efficient antibacterial agents with prolonged activity against various pathogens [ 2 ]. Recent studies have demonstrated that Ag NPs exhibit size- and shape-dependent antimicrobial activity [ 3 , 4 , 5 ]. In summary, small-sized Ag NPs (up to ~20 nm) demonstrated the highest bactericidal effects compared to larger counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the localized surface plasmon resonance effect, AgNPs have been used, for example, to color merino wool fibers, leading to novel AgNP-wool composite materials with different colors depending on AgNP size and their interaction with keratin from wool fibers ( Kelly and Johnston, 2011 ); nevertheless disinfectant features have been conferred to those fabrics ( Pietrzak et al, 2016 ). Numerous applications were developed in the life sciences research, based on AgNPs as source of silver, such as in pharmacy, cosmetics, sanitation, wastewater treatment, etc., ( Tylkowski et al, 2017 , Bapat et al, 2018 , Kaur et al, 2018 , Huang et al, 2020 , Al-Zubaidi et al, 2019 , Osonga et al, 2020 , Bernardo-Mazariegos et al, 2019 ). Generally silver ions were found to be the actual active agent, when released from silver nanoparticles (AgNPs) – since there is no final statement that nanoparticles themselves have antimicrobial or antifungal activity ( Ivask et al, 2014 , Mittelman et al, 2015 )).…”
Section: Introductionmentioning
confidence: 99%